Effect of Light-Emitting Diode (LED) lighting on growth development and physiology of lettuce (Lactuca sativa) - Jamaluddin, Asma Adila (2015)
Lettuce (Lactuca sativa) that belongs to the family Asteraceae originated from the Middle East, is a leafy vegetable type often plugged with pests and diseases as well as unfavourable weather conditions when planted outdoors. The objective of this study was to observe the effect of different LED light on growth and development of Lactuca sativa. The plants were grown on a plant rack equipped with LED lights at Physiology Laboratory, Department of Crop Science, Faculty of Agriculture. Four different light regimes consisted of Red and Blue LED as Treatment 1 (T1), Red and Blue LED with Fluorescent as Treatment 2 (T2), Red and Blue with Orange LED as Treatment 3 (T3) and Red and White LED as Treatment 4 (T4) were applied on the lettuce plants. At the onset of the experiments, seeds were directly sowed in cocopeat in plug trays, and placed in a container under the different light regimes for three weeks. Randomized Complete Block Design (RCBD) was used. The most effective results were observed in Treatment 1 with Red and Blue LED light treatment. The study showed that supplemental Fluorescent light affected high in plant morphology but low in its physiology, while supplemental Orange LED inhibited lettuce growth. Treatment without Blue light, gave the lowest yield.